`(2x - 1)^2 = 36`
`(2x - 1)^2 = 6^2` hoặc `(2x - 1)^2 = (-6)^2`
`2x - 1 = 6` hoặc `2x - 1 = -6`
`2x = 6 + 1` hoặc `2x = -6 + 1`
`2x = 7` hoặc `2x = -5`
`x = 7 : 2` hoặc `x = -5 : 2`
`x = 3,5` hoặc `x = -2,5`
\(\left(2x-1\right)^2=36\)
\(\Rightarrow\left(2x-1\right)^2=6^2\)
\(\Rightarrow\left[{}\begin{matrix}2x-1=6\\2x-1=-6\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2x=7\\2x=-5\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=\dfrac{7}{2}\\x=-\dfrac{5}{2}\end{matrix}\right.\)